The Effect of Trustworthiness, Attractiveness, Expertise, and Popularity of Celebrity Endorsement - Yolanda Mayang Sari; Rina Suthia Hayu; Muhartini Salim (Jurnal Manajemen dan Kewirausahaan, 2021)
This study aims to determine the impact of trust, attractiveness, expertise, and popularity (Suhay Salim) celebrity endorsement on the purchasing decisions of Korean skincare brand "Some By Mi" in Indonesia. The research method used in this research is quantitative research. Data was collected through an online questionnaire. This study involved 250 respondents who had bought and tried several skincare products "Some By Mi". Purposive sampling is used as a sampling strategy in this study, which uses a non-probability sampling methodology. Data collected from online questionnaires were analyzed using Multiple Linear Regression using SPSS 21.0 for Windows. The findings reveal that the trustworthiness, attractiveness, expertise, and popularity of celebrity endorsement Suhay Salim significantly and positively influence the public purchasing decision of Korean skincare brand ““Some By Mi”” partially.